SPERM-ZONA BINDING INTERACTION: AN IN SILICO BLUEPRINT TO IDENTIFY MARKER MOLECULES FOR EFFECTIVE FERTILIZATION (International Association of Biologicals and Computational Digest, 2022)
Precise binding interaction between sperm surface-specific molecules and the ovum zona-pellucida is the key to a positive fertilization outcome. An in-silico approach was therefore adopted to understand the intricate molecular docking between a receptor molecule of the Zona-pellucida (ZP3) and effective sperm ligands selected viz., IZUMO1, ADAM2 and ERp57. The study aims at identifying the possible molecular biomarkers on the sperm plasma membrane which could efficiently initiate the acrosome reaction, recognize and bind to barrier membrane molecules and mediate fusion of sperm with ovum, thus culminating in successful fertilization. The in-silico identification of sperm-oocyte interaction biomarkers would serve a dual purpose in aiding to recognise potential targets for fertility regulation and infertility research.
Keywords: ZP3 receptors, sperm ligands, fertilization, binding interaction, protein- protein docking.